PENGARUH MARKET ORIENTATION DAN TECHNOLOGY ORIENTATION TERHADAP BUSSINESS PERFORMANCE USAHA COFFE SHOP DI KABUPATEN BEKASI - Syahyono, Syahyono; Ramadhani, Dhaffa; Apif CH, Faisal; Sodik, Jafar; Risma, Risma (LP2M Universitas Bina Bangsa, 2025)
This study aims to explore the influence of market orientation and technology orientation on the business performance of coffee shop businesses in Bekasi Regency. This study uses a qualitative approach by collecting data through a questionnaire distributed to 150 respondents, who are coffee shop consumers. Respondents were selected using the purposive sampling method. The results of the study show that the application of market orientation and technology orientation synergistically contributes significantly to improving the performance of the coffee shop business. The results of the study show that orientation technology, such as the use of delivery service applications, makes it easier to buy coffee. As many respondents (58.45%) expressed their agreement. In addition, 81.2% of respondents felt that the ease of the coffee ordering process influenced their purchasing decision. Meanwhile, Market Orientation in this case has only 50.9% of influencers and 62.7% of advertising on consumer buying interest. This study provides practical implications for coffee shop managers to increase competitiveness through innovative market approaches and the use of technology. This finding is expected to be a strategic reference for small and medium enterprises in similar sectors.